Hygienic substantiation of selection criteria for fungicides’ monitoring in agro-industrial complex of Ukraine (Environment & Health, 2019)
Improvement of the pesticides’ monitoring system in the agro-industrial complex of Ukraine will ensure the preservation of the environment, protection of public health, and rational use of natural resources.Objective: We performed a hygienic substantiation of the selection criteria for fungicides’ monitoring in the agro-industrial complex of Ukraine.Materials and methods: We used the following methods: laboratory and full-scale field hygienic experiments, a method of statistical analysis, and physico-chemical (chromatographic), organoleptic, physical, mathematical modeling, mapping ones.Results and discussion: On the basis of long-term research of fungicides’ behaviour under soil-climatic conditions we have proposed selection criteria for the fungicides’ monitoring in various objects.To monitor pesticides in soil it was recommended to take into account Koc, ADI, the hazard class by fungicides toxicity, τ50 in soil, IPP and Ecotox in soil; in water – solubility in water, Koc, ADI, the hazard class by fungicides toxicity, τ95 in water, GUS, the risk magnitude of water contamination by pesticides; in the air – vapour pressure, ADI, the hazard class by fungicides’ toxicity, CIPP, occupational risk; in food – ADI, the hazard class by fungicides’ toxicity, τ50 in the agricultural raw materials.The monitoring of the fungicides was proposed to perform if the pesticides met at least three of listed criteria for each environment: water, soil, air, food.Conclusions: The criteria for the selection of fungicides, applied in the agro-industrial complex of Ukraine for the purpose of monitoring, were scientifically substantiated. Their implementation into the work of the appropriate ministries and departments will allow to preserve the health of agricultural workers and population on the whole and to reduce the anthropogenic burden on the environmental objects.
Keywords: fungicides; selection criteria; ADI; hazard class; persistency in environmental objects; monitoring